1983
DOI: 10.1002/1097-4679(198311)39:6<829::aid-jclp2270390604>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

MMPI code types and DSM-III diagnoses

Abstract: Examined the relationship of the MMPI high‐point codes and the diagnostic system of the Diagnostic Statistical Manual III of the American Psychiatric Association. Five psychiatrists reanalyzed the patients' records and rendered a DSM‐III diagnosis. In all, 24 code types were identified from the private psychiatric clinic sample (N = 261). The resulting clusters of diagnostic classification are presented, and, additionally, a narrative summation for each code type is given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 4 publications
2
25
0
Order By: Relevance
“…An example from MMPI literature of an avoidant personality bridge would be the 28-code type which combines the neurotic elements of the MMPI 2 scale with the withdrawn aspects of the MMPI scale 8. In a recent study 40% of those with the 28 MMPI code type were seen as having an avoidant personality (Vincent et al, 1983).…”
supporting
confidence: 79%
See 1 more Smart Citation
“…An example from MMPI literature of an avoidant personality bridge would be the 28-code type which combines the neurotic elements of the MMPI 2 scale with the withdrawn aspects of the MMPI scale 8. In a recent study 40% of those with the 28 MMPI code type were seen as having an avoidant personality (Vincent et al, 1983).…”
supporting
confidence: 79%
“…Studies of the MMPI 274code type describe passive aggressive personalities the primary personality disorder of this code type (Gilberstadt & Duker, 1965;Marks, Seeman, & Haller, 1974). Using the DSM-III rather than earlier classifications systems, Vincent et al (1983) found that 64% of individuals with the 247 code type were seen as evidencing a passive aggressive personality.…”
mentioning
confidence: 99%
“…The diagnosticians reviewed information obtained from structured research interviews with the Schedule for Affective Disorders and Schizophrenia (64) and from systematic record reviews. The healthy comparison subjects received a brief clinical interview and were administered the MMPI-168 to screen for current psychopathological disorders; they were included if the T score was less than or equal to 70 (65).…”
Section: Diagnostic Assessmentmentioning
confidence: 99%
“…This cutoff point is somewhat more stringent than those used in similar studies examining MMPI overlap with other measures of psychopathology (Gilberstadt & Duker, 1965;Kelly & King, 1977;Vincent et al, 1983); it was felt that this criterion would reduce the possibility of any groups emerging by chance. Of the total sample tested, 8.3% (n = 272) were found to have MMPI Scales 7 and 8 as their Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…It is important at this point to state the precautions and goals that we have applied to our research paradigm to prevent this sort of outcome. Regarding precautions, we reiterate that membership in one of the MCMI-MMPI subgroups was restricted to those MCMI 2-point code types that included at least 15 cases, which is an entry criterion more stringent than that used in similar studies (Gilberstadt & Duker, 1965;Vincent et al, 1983). This should reduce the likelihood that incidental subgroups will emerge by chance and, in so doing, will prevent the genesis of meaningless classifications.…”
Section: Methodological Considerationsmentioning
confidence: 99%